TAFSIR MUBĀDALAH: Addressing Gender Issue in Family Planning Programs From Qur’anic Perspective - Saiful Khair, Muhammad; Faridatunnisa, Nor; Irawan, Rendi; Hidayah, Falakul; Digdayani, Tasya Avanti; Mualimin, Mualimin (Faculty of Ushuluddin and Religious Studies UIN Sulthan Thaha Saifuddin Jambi, 2025)
In the Indonesian context, the implementation of the Family Planning program, commonly referred to as KB, inherently involves gender issues. Due to the prevailing mindset among the public that “the main consumers of this program are women.” This situation certainly has negative implications. Women, who have long been regarded as the primary bearers of responsibility in the domestic sphere, must also contend with the side effects of contraceptive use, such as significant physical and psychological changes. The changes women experience as a result of contraceptive use often become the primary reason for men’s dissatisfaction, thereby further marginalizing women’s positions. This paper aims to re-examine this stigma through the lens of Islam and to examine whether the contraception program is only the responsibility of women. This qualitative research uses Faqihuddin Abdul Kodir's mubādalah (reciprocal) theory as its analytical tool. Based on the study, it was found that Islam does not explicitly specify which gender should use contraception. Islam emphasizes that responsibility in a household, especially in the context of contraception, is not limited to a particular party. Instead, all complement each other, noting that all decisions result from communication and mutual deliberation, where all impacts and consequences that arise later have been discussed so that no party is burdened or disadvantaged.